Understanding the Relationship Between South Pacific Oscillation and ENSO - Suqiong Hu; Wenjun Zhang; Feng Jiang (Geophysical Research Letters)
Abstract The boreal summer South Pacific Oscillation (SPO), the dominant mode of atmospheric variability over the South Pacific, has been proposed as a potential precursor to the development of El Niño‐Southern Oscillation (ENSO). However, this study demonstrates that the SPO signal during the developing summer of ENSO events is primarily driven by the concurrent ENSO‐related tropical Pacific sea surface temperature anomalies, challenging its role as an independent predictor of ENSO. We further show that those winter ENSO events preceded by a summer SPO signal begin to develop before the SPO signal in the extratropics appear, and incorporating the summer SPO signal into ENSO persitence model does not add additional information for ENSO hindcast. The observational findings are further corroborated by evidence that the lead relationship of SPO over ENSO in climate models is mainly determined by their simulated ENSO teleconnection to SPO during summer.